Atomically dispersed materials for rechargeable batteries. (October 2020) - Zhang, Zhiqi; Liu, Jiapeng; Curcio, Antonino; Wang, Yuhao; Wu, Junxiong; Zhou, Guodong; Tang, Zhenghua; Ciucci, Francesco
Abstract: Rechargeable batteries have significantly helped to effectively use renewable energy sources as well as to intensively expand the electrification of vehicles. To achieve such goals, new advanced materials are urgently required. Atomically dispersed materials (ADMs) with single-atom metals supported on substrates feature uniform metallic sites and represent the utmost utilization of atoms, demonstrating wide applications in catalysis. These structural and morphological characteristics also make ADMs attractive materials for rechargeable batteries. Herein, we highlight and summarize the recent advances in synthetic methods for ADMs by physical confinement and chemical bonding. Subsequently, we summarize the recent progress in the design of diverse ADMs for lithium metal, lithium-sulfur, sodium-sulfur, lithium-oxygen, and zinc-air batteries and unveil the corresponding roles of ADMs from atomistic perspectives. Finally, the challenges and perspectives in this field are discussed. Graphical abstract: We review how ADMs (mainly M-N-C electrode materials) have been i) synthesized; ii) characterized; iii) studied with atomistic calculations, including density functional theory (DFT); and iv) applied to Li-metal, Li–S, sodium-sulfur (Na–S), Li–O2, and Zn-air batteries. Challenges and perspectives in the field are also discussed. Image 1 Highlights: We reviewed the recent advances in the synthesis of ADMs, including physical confinement and chemical bonding. We overviewed the recent progress on the use of ADMs in Li-metal, Li-S, Na-S, Li-oxygen and Zn-air batteries. We reviewed computational works that have studied ADMs from a first-principles perspective. Challenges and perspectives are discussed.